Penggunaan Whatsapp sebagai Media Komunikasi Pacaran Jarak Jauh - Hartati Lambuan; Mas’amah Mas’amah; Mariana A. N. Letuna (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2019)
Long-Distance Relationship requires an effective communication process between the two to maintain relationships. So far there have been many negative assumptions about long-distance relationships. Most people doubt the success of long-distance relationships due to time constraints to meet and communicate directly. However, along with the development of communication technology, distance is not a barrier to establish relationship. The purpose of this study is to find out the use of WhatsApp as a communication medium for a long-distance relationship, also to find out the obstacles and solutions in establishing a long-distance relationship by students of the Communication Science Study Program. The theory used in this study is the Social Penetration Theory. The method in this study uses the Phenomenology method. While data analysis uses an Interactive Analysis model by Miles and Huberman, and the determining informants' technique using Purposive Sampling techniques. The result of the study indicates that Whatsapp is considered very helpful for long-distance relationships, especially features like video-call, voice-call, chatting, and emoticon that helps to express feelings, self-disclosure, build trust, strengthen commitment, and also maintain communication. The obstacle in using Whatsapp such as pirated Whatsapp use, typing errors, incorrect punctuation, use of emoticon that are different from the message, and network constraints. The solutions to reducing misunderstandings are become wiser in using Whatsapp, understanding partner and hold back more, also keep communicating to minimize misunderstanding so the relationship can be maintained.